IMPLEMENTASI TAHAPAN PEMBELAJARAN MENDALAM (MEMAHAMI-MENERAPKAN-MEREFLEKSI) DALAM PENINGKATAN KUALITAS TULISAN NARATIF SISWA - Noprianti; Fawilda Yanti, Nur; Silviyanti Saputri, Mince; Candra Dewi, Anita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the implementation of the stages of deep learning, understanding, applying, and reflecting in improving the quality of students' narrative writing which is still low, especially in text structure, idea development, and language accuracy due to conventional approaches that focus on the final result. Using a literature study method with a descriptive-analytical approach, data was obtained from journals, books, and relevant research through the stages of identification, selection, analysis, and synthesis. The results of the study show that the three stages significantly improve the quality of narrative writing: the understanding stage strengthens the conceptual basis, the applying stage develops skills through structured practice, and the reflecting stage allows for evaluation and revision. The integration of the three not only improves the technical aspects of writing, but also creativity, critical thinking, and metacognitive awareness, so that deep learning is proven to be effective as an innovative, student-centered strategy and supports sustainable literacy development.